Beyond the Letter of His Master’s Thought : C.N.R. McCoy on Medieval Political Theory - P.Haggerty, William (Laval théologique et philosophique, 2008)
Published in 1962, Charles N.R. McCoy’s The Structure of Political Thought remains an important, albeit neglected, work on the history of political philosophy. Though there has been some appreciation of his study, there has never been a critical examination of his treatment of medieval political theory. In my paper, I explore the structure of his argument in the two chapters on medieval thought, showing how McCoy centers his discussion on an investigation of the different interpretative methods Thomas Aquinas and Marsilius of Padua employ when reading Aristotle. He does so in order to establish how the Aristotelian teaching — concerning the structure of political thought — is best protected by (and fulfilled within) revelation.